Organizational Success from the Perspective of the Learning Organization and Innovative Organization - Sawangrat, Nilawan (Journal of Industrial Business Administration, 2020)
The purposes of this research were 1) to study the learning organization, innovative organization and the success of the organization 2 ) to study the influence of the learning organization, innovation organization that affect the success of the organization. We use a quantitative research, data were collected by a questionnaire with 300 sample size in the Food processing industry in Rayong Province and analyzed by statistics: percentage, standard deviation, coefficient of variation and structural equation model. The results of the research showed that the success of the organization has an average value at a high level, followed by the organization of learning and innovation. For the coefficient of variation (CV), the average value is between 0.017-0.251 indicated the data has low variation or the data providers have similar opinions, and the analysis of the influence line between variables from the Structural Equation Model (SEM) found that the probability value (p- value) is equal to 1.079, Relative Chi-Square: CMIN / DF) is equal to 1.820. The Goodness of Fit Index (GFI) is 1.980 and the Root Mean Square Error of Approximation (RMSEA) is 0.060 which meets the requirements of Specific criteria which can be concluded that the influence lines between the variables are concordant with the data from the literature review.